Effect of surfactants on jet break-up in drop-on-demand inkjet printing - Antonopoulou, E; Harlen, O; Rump, M; Segers, T; Walkley, M (AIP Publishing, 2021)
Jet formation and break-up in inkjet printing has been studied and understood mainly for pure liquids. Questions remain as to the role of surfactants on the inkjet printing process at the microsecond timescale. Here, numerical and experimental results demonstrating the effects of surfactants on jet break-up and drop formation at the scales relevant to drop-on-demand inkjet printing are presented. The rapid expansion of the free surface during the fast jetting process results in a depletion of surfactants along the air-liquid interface, resulting in surface tension gradients. During ejection, surfactants are concentrated towards the head of the droplet, while the trailing ligament is found to be almost devoid of surfactants. As a consequence, the initial evolution and pinch-off of the jet from the nozzle is found to be very similar to that of pure water, even though the equilibrium surface tension of the surfactant solution is lower by a factor of two. However, particularly for strong surfactants, Marangoni forces arising from surface tension gradients between the head drop and the ligament are found to delay, and can even prevent, the break-up of the main drop from the ligament thereby inhibiting the formation of satellite drops.